EFFECT OF EXPERIMENTAL VARIATION OF TEMPERATURE ON SERUM TRIGLYCERIDES IN UROMASTYX HARDWICKII - Malik, Samina; Qureshi, Ghazala; Dilawar, Aalia (Pakistan Journal of Physiology, 2018)
Background: The study has been performed on Uromastyx hardwickii, a local lacertilian species. This male Poikilotherm vertebrate mainly inhabits the arid regions of the Indo-Pakistan subcontinent. The objective of this study was to see whether artificially created high temperature in winter can increase triglycerides level in this species, as it is normally seen in summers. Material and Methods: This study was conducted in Oct 2005 and Jan 2006 in Physiology Lab, University of Health Sciences, Lahore. Male Uromastyx hardwickii (n=20) were kept for this study carried out in autumn and winter within 48 hours of their arrival in the laboratory. Blood samples were collected by anterior abdominal venepuncture from conscious animals using a heparinised syringe and serum Triglyceride was measured by GPO-PAP method (Human, Weisbaden, Germany). Results: Mean serum Triacylglycerol levels were found to be significantly higher in summer and with an increase in temperature observed during winter and autumn season. Conclusion: There is significant increase in serum triglycerides in Uromastyx hardwickii on artificial increase in temperature even during winter season.